Kontribusi Maqasid Syariah dalam Penetapan Hukuman pada Fiqih Jinayat - Muhammad Hidayat; Dinda; Mhd Irsan Akbar; Lulu Malona Siregar; Muhammad Raja (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The imposition of sanctions in fiqh jināyat (Islamic criminal law) is inseparable from the values and objectives embedded in Maqāṣid al‑Sharīʿah, which aim to realize the common good and ensure the establishment of justice for all humankind. This article aims to explain the role of Maqāṣid al‑Sharīʿah in determining the forms and measures of ʿuqūbāt (penalties) in fiqh jināyat, ensuring that the application of criminal sanctions is not merely retributive but also incorporates the values of prevention, education, and rehabilitation. Through a descriptive‑analytical approach and a literature review method, this discussion focuses on the concept of Maqāṣid al‑Sharīʿah, the classification of penalties in fiqh jināyat, and the relevance of maqāṣid values in shaping more adaptive forms of ʿuqūbāt in the contemporary era. The results of this study reveal that Maqāṣid al‑Sharīʿah serves as a normative foundation that guides the application of criminal penalties in upholding substantive justice. In this context, the implementation of ʿuqūbāt not only acts as a deterrent for offenders, but also protects the five fundamental necessities of human life religion, life, intellect, lineage, and property from all forms of abuse. Grounded in the maqāṣid values, the Islamic criminal justice system can respond to the evolving challenges of the times, including the need to create social harmony and sustainable justice for all segments of society.